ChemInform Abstract: [HMIM][Br9]: A Room‐Temperature Ionic Liquid Based on a Polybromide Anion. Issue 4 (28th January 2014) - Haller, Heike; Hog, Michael; Scholz, Franziska; Scherer, Harald; Krossing, Ingo; Riedel, Sebastian
Abstract [hmim][Br9] is prepared by addition of Br2 to [hmim]Br in a molar ratio of 5:1 (‐40 °C, 72 h).